2021
DOI: 10.1200/jco.20.03611
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of PET Response–Adapted Combined Modality Therapy for Esophageal Cancer: Mature Results of the CALGB 80803 (Alliance) Trial

Abstract: PURPOSE To evaluate the use of early assessment of chemotherapy responsiveness by positron emission tomography (PET) imaging to tailor therapy in patients with esophageal and esophagogastric junction adenocarcinoma. METHODS After baseline PET, patients were randomly assigned to an induction chemotherapy regimen: modified oxaliplatin, leucovorin, and fluorouracil (FOLFOX) or carboplatin-paclitaxel (CP). Repeat PET was performed after induction; change in maximum standardized uptake value (SUV) from baseline was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 25 publications
1
54
1
2
Order By: Relevance
“…Similarly, in the CALBG 80803 trial, no significant difference in the rate of PET-response was seen between FOLFOX and carboplatin/paclitaxel (64.9% versus 56.1%). 13 This observation confirms that PET-response is a sustainable predictor of tumour chemosensitivity and to a large extent independent from variations in platinum-based chemotherapy regimens. Accordingly, Ott et al 7 reported that PET-response was the only independent factor predicting recurrence ( p = 0.018) in a group of completely resected (R0) patients with oesophago-gastric cancer.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, in the CALBG 80803 trial, no significant difference in the rate of PET-response was seen between FOLFOX and carboplatin/paclitaxel (64.9% versus 56.1%). 13 This observation confirms that PET-response is a sustainable predictor of tumour chemosensitivity and to a large extent independent from variations in platinum-based chemotherapy regimens. Accordingly, Ott et al 7 reported that PET-response was the only independent factor predicting recurrence ( p = 0.018) in a group of completely resected (R0) patients with oesophago-gastric cancer.…”
Section: Discussionsupporting
confidence: 67%
“… 7 In the consecutive MUNICON I and II studies, the same group of investigators demonstrated that an early metabolic response-guided treatment algorithm identifies non-responding patients and allows for the adjustment of the perioperative treatment strategy. 8 , 9 Since then, several other groups developed response-guided treatment algorithms with some modifications in methodology, endpoints and trial designs 10 13 but implementation into clinical practice is still lagging behind.…”
Section: Introductionmentioning
confidence: 99%
“…Other positron emission tomography strategy (CALGB 80803) was recently published and will need further development. 15 Many studies have documented resistance to therapy (chemotherapy and or chemoradiation) in the presence of CSCs and enrichment of CSCs in the residual resistant cancer. 13,[16][17][18][19][20] Will we ever be able to customize approach for an individual patient?…”
Section: Therapy Resistancementioning
confidence: 99%
“…Data from CALGB 80803 and my institution further confirm that carboplatin-paclitaxel is a suboptimal regimen to achieve micrometastatic control in EAC. 7,8 Radiation may improve local control in cases of lower-quality surgical resections (almost half of patients in the CROSS trial underwent transhiatal esophagectomy! ), but the prospect of preserving the esophagus through the use of chemoradiation-which the authors argue is possible-appears to be a mirage as elusive as the meaning Although CROSS retains a role for esophageal squamous cell carcinoma, better systemic options exist for adenocarcinoma, for which high-quality surgical resection remains a mainstay of treatment.…”
Section: Daniela Molena MDmentioning
confidence: 99%